2021
DOI: 10.23887/jippg.v4i3.39838
|View full text |Cite
|
Sign up to set email alerts
|

Improve Students' Listening Comprehension Through Podcasts

Abstract: Dalam mengatasi masalah dan kesulitan yang dihadapi oleh sebagian besar siswa dalam belajar mendengarkan, beberapa akademisi dan spesialis bahasa Inggris dalam pengajaran memutuskan untuk memperhatikan pendekatan, metode, dan teknik yang paling efektif untuk membantu siswa mereka dalam belajar mendengarkan. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan podcast dalam metode mendengarkan bahasa Inggris terhadap pemahaman mendengarkan siswa. Metode yang digunakan adalah metode kuantitatif dengan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…According to the results of the study, the listening comprehension of students who listened to podcasts increased compared to students who did not listen to podcasts. Furthermore, the results of the research are compatible Hadi (2021) who analyzed the effect of using podcasts on students' listening comprehension. The finding showed that the use of podcasts had a huge impact and beneficial influence towards students' listening skill.…”
Section: Discussionsupporting
confidence: 62%
“…According to the results of the study, the listening comprehension of students who listened to podcasts increased compared to students who did not listen to podcasts. Furthermore, the results of the research are compatible Hadi (2021) who analyzed the effect of using podcasts on students' listening comprehension. The finding showed that the use of podcasts had a huge impact and beneficial influence towards students' listening skill.…”
Section: Discussionsupporting
confidence: 62%